Methodology of historical philosophical research within the context of current philosophical process - Stepanov, Viacheslav; Chebotnikova, Maria (Skhid, 2016)
In the domain of the Ukrainian history of philosophy one can clearly observe symptoms of eclecticism, contamination, and methodological ambiguity. Such situation is rooted in continuous insufficiency of the methodological framework of Ukrainian philosophy, split by competing ideological structures. Critical condition of humanitarian epistemology is aggravated by the urgent need to overtake foreign studies in the corresponding field, which constantly increase in number and evolve in character. The article aims at critical assessment of methodological approaches to historical philosophical analysis within the light of current philosophical studies. Analysis of the relevant literature on the problem of how to identify the character of interference between the target philosophical discourse and the discourse of the historical reconstruction allowed revealing the critical lines of relativist archeology and traditional historiography. Relativist approach is averted from the dimension of concrete texts to logical anachronistic speculations over seemingly evident contextual links. Such strategy is legitimate to sustain logical descriptions of the categories exempted from the certain paradigm but it is useless to reveal factual genealogical links between the discourses of the two philosophers. Descriptive studies seem to fall prey to hermeneutic ambiguity in referring to a set of ideas forming the canon of perennial philosophy. It is proved that historiographical approach enables to objectively examine genetic relations between various corpora of philosophical texts. Nowadays the Ukrainian historico-philosophical science is going through a harsh crisis of methodology, caused by distortion of universal coordinates of scientific thinking allegedly providing the condition of the so-called methodological pluralism. Numerous discussions focus on the question about the very scientific nature of history of philosophy as a branch of knowledge. The tendency which appears to prevail in such disputes defines history of philosophy as philosophy in contrast to the opinion that history of philosophy should be rather seen as approximate to social history.